Análisis de los medios sociales como una herramienta para promover el negocio, Industria Maderero El Roble - Villavicencio Rizzo, Elvira Victoria (2020)
The purpose of the research lies in Studying social media as a tool to promote business; El ROBLE Timber Industry since today's users are influenced by the criteria disseminated through the networks when acquiring and opting for services over the internet, transforming them into marketing tools of great importance. Social media has been impacted within technology with various aspects of image and quantity of sales, leading small and large companies to exploit their products properly. Individuals have become so hooked on social media that over time the environment has been changing drastically, modifying existing businesses, to get a better service, having a tangible impact, making all or at least the majority of macro and micro companies enter the world of social media. The conclusions of the case study will be structured in the form of strategies that approve the oak timber industry to integrate social networks in its marketing activities, allowing to better know, know and understand customers, to have good communication and interact with everyone them and thus achieve a good result in terms of profits, this helps to amplify the importance of your brand and of course its recognition.